Miles Black: capstone - Black, Miles, artist (Colorado State University. Libraries, 2016)
The artist's statement: As an artist, I strive to create design work that has an incorporation of fine art. Starting my artistic career as a painter, I studied form and color in depth, which are now the elements I focus on in design. I believe design has become extremely rigid and simple, motivating me to combine my artistic skills with computer tools to create true art for the business world. Through my design, I plan to send positive messages and work for progressive companies that are working to make a change for the better in this world. Design is everywhere, and through this art form I can see endless possibilities in the future.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design